Inversiones a plazo fijo y su incidencia en la gestión financiera de la Cooperativa de Ahorro y Crédito San Jorge Ltda. de la Provincia de Chimborazo período, 2022. - Conde Calderón, Janina Lizeth (2025)
The objective of the research was to analyze the fixed-term investments and their impact on the financial management of Cooperativa de Ahorro y Crédito San Jorge Ltda. In the province of Chimborazo for the period 2022. The methodology applied was deductive with a quantitative approach where data collection was used by applying field and documentary research. Interviews were conducted to obtain relevant information on fixed-term investments. Documentary research was used to analyze the financial statements and fixed-term deposit rates. The results of the research show the monthly variation of fixed-term investments in the cooperative with a fluctuating behavior with a tendency to growth in the period analyzed, the initial investment amount in January was USD 6,463,030.27, while in December it closed at USD 7,193,184.20, reflecting an overall increase of USD 730,153.93, equivalent to 11.30%. The calculated financial indicators, such as current liquidity, suggest that the cooperative may face difficulties in meeting its short-term obligations due to the low availability of liquid assets, as evidenced in the liquidity ratios. ROE and ROA indicated low profitability and efficiency in the use of equity and assets respectively, the internal study revealed that fixed-term investments are a fundamental component of the cooperative's portfolio relevant information to be able to issue a criterion regarding the entity's financial management. In conclusion, fixed-term investments showed growth during the period analyzed, but profitability indicators such as ROE and ROA showed low results, indicating limited efficiency in the use of the entity's equity and assets; therefore, it is crucial that the cooperative implement strategies focused on improving its liquidity and profitability, evaluating alternatives that diversify liquid assets and increase efficiency in the use of resources to ensure greater sustainability and financial stability in the long term.